2022
DOI: 10.1177/08902070211072745
|View full text |Cite
|
Sign up to set email alerts
|

Interdependencies between family and friends in daily life: Personality differences and associations with affective well-being across the lifespan

Abstract: Family and friends are central to human life and well-being. Most people maintain both family and friendship relationships and these relationships might show interdependencies that have scarcely been addressed. We examined the relative frequency of daily contact with family and friends (i.e. friends/family-contact) and its link with personality traits and affective well-being. In an experience sampling study with 396 participants ( Mage= 40 years, range 14–88 years, 52% females), we studied how friends/family-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
3
8
0
Order By: Relevance
“…Confirming previous research, individuals across all studies reported the highest momentary well-being after interactions with close peers (Buijs et al, 2022; Kahneman et al, 2004; Quoidbach et al, 2019; Vogel et al, 2017). Interactions with family members and weak ties were also related to higher well-being within persons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Confirming previous research, individuals across all studies reported the highest momentary well-being after interactions with close peers (Buijs et al, 2022; Kahneman et al, 2004; Quoidbach et al, 2019; Vogel et al, 2017). Interactions with family members and weak ties were also related to higher well-being within persons.…”
Section: Discussionsupporting
confidence: 88%
“…Empirical studies comparing the effects of different interaction partners found that interactions with strong ties were associated with more positive affect than interactions with weak ties (e.g., Venaglia & Lemay, 2017). Within the category of strong ties, interactions with friends (a large subgroup of the category close peers ) were associated with more positive affect than interactions with family members (Buijs et al, 2022; Kahneman et al, 2004; Quoidbach et al, 2019; Vogel et al, 2017). One possible explanation for this finding is that interactions with friends are more reciprocal and voluntary in nature and typically involve more fun leisure activities and less everyday duties than interactions with family members (Hudson et al, 2020; Larson et al, 1986; Vogel et al, 2017).…”
Section: Definition and Measurement Of Well-beingmentioning
confidence: 99%
“…Confirming previous research, individuals across all studies reported the highest momentary well-being after interactions with close peers (Buijs et al, 2022;Kahnemann et al, 2004;Quoidbach et al, 2019;Vogel et al, 2017). Interactions with family members and weak ties were also related to higher well-being within persons.…”
Section: Interactions With Close Peers Associated With Highest Moment...supporting
confidence: 85%
“…On the basis of these results, decreases in the proportion of interactions with friends may be linked to lower well-being. In addition, previous research has suggested that more extraverted individuals profit comparatively more strongly from interactions with friends than from interactions with other interaction partners (Buijs et al, 2023). Thus, more extraverted individuals could suffer more from a reduction in interactions with friends than less extraverted individuals.…”
Section: Effects Of Extraversionmentioning
confidence: 99%